The Effectiveness of Leadership in Islamic Education Management in The Digital Era - Muhammad Haiqal; Mukhsin Nuzula; Winda Safitri; Nisaul Khaira (Jurnal Serambi Ilmu, 2025)
This study highlights the importance of leadership effectiveness in Islamic education management within the digital era, focusing on the integration of Islamic values and the utilization of information technology. The findings reveal that the application of Islamic principles such as honesty, justice, and ihsan (excellence in conduct) by leaders, when combined with the use of digital technology, can foster an adaptive and innovative learning environment. Furthermore, digital communication skills and the ability to build strong online networks play a crucial role in establishing trust and loyalty among staff and students. Managerial competencies in data-driven strategic decision-making and digital resource management are key factors in achieving educational goals. This study emphasizes that stakeholder support and technological infrastructure significantly influence leadership effectiveness. Therefore, the success of Islamic education management in the digital age depends on the synergy between Islamic values, managerial competence, and technological adaptation to optimize the achievement of institutional vision and mission. The implications of this research underline the urgency of digital leadership training for leaders of Islamic educational institutions to effectively navigate contemporary challenges.